ANALISIS JAMINAN KESEHATAN DALAM PERSPEKTIF NEGARA KELAS - Arya M Albery; Annisa Saliha; Lusi Puspika Sari; Tamrin; Huda Abshar Abdhallah; Lidia Dwi Syaputri (Madika: Jurnal Politik dan Governance, 2023)
The state plays a very important role and has an obligation to meet the needs of its people, one of which is in the form of the obligation to fulfill public health services in the country. Thie analysis used the perspective of a Marxist class state, namely the existence of social classes in society, regarding the existence of social class divisions that arise from the existence of modes of production, as controllers of the production system (owners of capital) and producers who provide direct services for the dominant class (workers). Karl Marx (1818-1883) saw that actually the main actors who play an important role in the survival of a society are social classes. The alienation experienced by humans is actually the result of the oppression of one class by another class. To eliminate these exploitative actions, Karl Marx put forward a class struggle or revolution. Karl Marx believed that the classes that were formed in a society could be removed by this revolution so that justice could be upheld. The purpose of this study is to see and find out the perspective of country class put forward by Marx on how a country fulfills its responsibilities in terms of health services, namely health insurance. The research method used is a descriptive qualitative research method, using data collection techniques through observation or observation and interviews.